A Strategy of Enhancing the Photoactivity of g‑C3N4 via Doping of Nonmetal Elements: A First-Principles Study - Ma, Xinguo; Lv, Yanhui; Xu, Jing; Liu, Yanfang; Zhang, Ruiqin; Zhu, Yongfa (Journal of physical chemistry. C, 2012)
An effective structural doping approach has been described to modify the photoelectrochemical properties of g-C3N4 by doping with nonmetal (sulfur or phosphorus) impurities. Here, the substitutional and interstitial doped models of g-C3N4 systems were constructed with different doped sites, and then their dopant formation energies and electronic properties were performed to study the stability and visible-light photoactivity using first-principles density functional theory, respectively. Our results have identified that an S atom preferentially substitutes for the edge N atom of g-C3N4; however, a P atom preferentially situates the interstitial sites of in-planar of g-C3N4. Furthermore, it is demonstrated that the doping with nonmetal impurities reduces the energy gap to enhance the visible-light absorption of g-C3N4. The increased dispersion of the contour distribution of the HOMO and LUMO brought by doping facilitates the enhancement of the carrier mobility, while the noncoplanar HOMO and LUMO favor the separation of photogenerated electron–hole pairs. Especially, P interstitial doping shows a prominent potential due to the appearance of a new channel for carrier migration. It should be pointed out that the proper doping form should be controlled, so that reasonable photoelectrochemical properties can be achieved.